Assessing the Impacts of Climate Change on Meteorology and Air Stagnation in China Using a Dynamical Downscaling Method - Hu, Anqi; Xie, Xiaodong; Gong, Kangjia; Hou, Yuhui; Zhao, Zhan; Hu, Jianlin (Frontiers in Environmental Science, 2022)
This study utilizes the Weather Research and Forecasting model with a higher resolution (36 km × 36 km) to dynamically downscale the Community Earth System Model results forced by the three representative concentration pathways (RCP) scenarios (RCP4.5, RCP6.0, and RCP8.5) over China. The goal was to compare meteorological fields during the present (2006–2015) and future (2046–2055) climatological periods. An appropriate air stagnation judgment index was selected to explore the effect of climate change on air quality-related meteorological conditions. The results show that the occurrence of wintertime air stagnation over China in the middle of this century (2046–2055) will reduce slightly, with the largest reduction projected under the RCP8.5 scenario (−4 times). However, long-lasting air stagnation events (ASE) are projected to increase in the future, and this increasing trend is more obvious under the RCP8.5 scenario. The projected increase in the long-lasting ASE in different regions of China ranges from 3 to 11 times. Among these, Central China has the largest increase, followed by East and Northeast China, while South China has the lowest increase in ASE. Our results indicate that more attention should be dedicated to extreme pollution events that may potentially be caused by long-lasting air stagnation events in the future.